2008
DOI: 10.1021/om8004405
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Reaction of Silanol and Triarylborane: Boron−Aryl Bond Cleavage and Formation of a Si−O−B Heterocyle

Abstract: o-(Hydroxydimethylsilyl)(dimesitylboryl)benzene (1) underwent intramolecular cyclization to give 5,5dimesityl-2,2-dimethyl-3,4-benzo-1,2,5-oxasilaboracyclopentene (4) and mesitylene by boron-aryl bond cleavage. Whereas triethylamine as an additive accelerated the cyclization, DBU stabilized a silyloxyborate complex, 1,8-diazabicyclo[5.4.0]-7-undecenium 5,5-dimesityl-2,2-dimethyl-3,4-benzo-1,2,5-oxasilaboratacyclopentene, which was characterized by X-ray crystallographic analysis and HF calculations. The deuter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Recently, we synthesized o -(hydrosilyl)­(diarylboryl)­benzene, 1 , in which the dimesitylboryl and hydrosilyl groups were linked through an o -phenylene skeleton . The Si–H bond was activated by the boryl group for several types of reactions (Scheme ): (i) dehydrogenative condensation with alcohols to form 2 (R = Me ( a ); i -Pr ( b )), (ii) nucleophilic displacement by a fluoride ion to form 3 , and (iii) H-Mes exchange between the hydrogen atom on the Si atom and mesityl (Mes) group on the boron atom…”
Section: Introductionmentioning
confidence: 91%
“…Recently, we synthesized o -(hydrosilyl)­(diarylboryl)­benzene, 1 , in which the dimesitylboryl and hydrosilyl groups were linked through an o -phenylene skeleton . The Si–H bond was activated by the boryl group for several types of reactions (Scheme ): (i) dehydrogenative condensation with alcohols to form 2 (R = Me ( a ); i -Pr ( b )), (ii) nucleophilic displacement by a fluoride ion to form 3 , and (iii) H-Mes exchange between the hydrogen atom on the Si atom and mesityl (Mes) group on the boron atom…”
Section: Introductionmentioning
confidence: 91%
“…Benzosiloxaboroles are silicon analogues of benzoxaboroles where the carbon atom in a boracyclic ring is replaced by a silicon atom, thus resulting in the formation of a B-O-Si linkage. The first benzosiloxaborole derivative bearing mesityl group at the boron atom (49) was synthesized in 2008 (Scheme 17) [37,38]. The starting 1-dimesitylboryl-2-(dimethylsilyl) benzene (47) was subjected to hydrolysis of the Si-H bond followed by ring closure effected through an attack of silanol on one of the B-Mes bonds, yielding mesitylene as a byproduct.…”
Section: Benzosiloxaboroles and Related Ring-expanded Systems Comprising B-o-si Linkagementioning
confidence: 99%
“…Scheme 13. Synthesis and transformation of a boracyclic system (38) featuring B-O-B linkage attached to bicyclohexene-peri-naphthalene scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter reaction mesitylene is formed due to the B Mes bond cleavage effected by the the hydroxyl proton. It was found that the protonolysis was accelerated by NEt 3 where as the addition of DBU stabilized a crystalline silyloxyborate complex 132 (Scheme 56) [123].…”
Section: Formation Of 34-benzo-125-oxasilaboracyclopentenesmentioning
confidence: 99%